To Investigate Premenopausal and Postmenopausal Women for Evaluation of their Serum Calcium, Calcitonin and Parathormone Levels (Medical Forum Monthly, 2021)
Objective: To investigate premenopausal and postmenopausal groups of women and evaluate their serum levels of Calcium, Calcitonin and Parathormone.Study Design: Cross-sectional/ Observational StudyPlace and Duration of Study: This study was conducted at the Department of Physiology at Khyber Medical College/Teaching Hospital in Peshawar from April, 2020 to October, 2020.Materials and Methods: 100 Subjects were included according to the Inclusion criteria. The subjects were divided into two groups: Group I (Premenopausal Women) and Group II (Postmenopausal Women). Blood for Calcium, Calcitonin and Parathormone Levels was taken and analysed at the Hospital Lab. All information was recorded using proforma and analysed on SPSS for MacBook, Version 26.0.Results: Mean and standard deviations for age were recorded as 34.5 ± 10.1. The Mean and standard deviations for the levels of Serum Calcium (taken in mg/dl) were recorded as 9.74 ± 0.56 for Group I (Premenopausal Women) and 7.92 ± 0.72 for Group II (Postmenopausal Women), Serum Parathormone (taken in pg/ml) were recorded as 31.29 ± 18.56 for Group I (Premenopausal Women) and 60.16 ± 42.63for Group II (Postmenopausal Women) and Serum Calcitonin (taken in pg/ml) were recorded as 5.8 ± 3.02 for Group I (Premenopausal Women) and 5.1 ± 1.98 for Group II (Postmenopausal Women).Conclusion: Our study finds out that Calcium levels were lower in the Postmenopausal women (Group I) with significantly higher parathormone levels. This has a strong correlation and suggests an increased bone turnover.